Measurement of the average shear rate around a microparticle in the shear thinning medium with laser tweezers. (4th July 2018) - Domagalski, Piotr; Dziubinski, Marek; Pawlak, Ryszard; Tomczyk, Mariusz
ABSTRACT: A novel method for the determination of the average shear rate around a microparticle moving in the fluid is presented. Although the shear rate around a particle moving in the fluid is a parameter of paramount importance in sedimentation studies, its determination is time-consuming, thus model-based solutions are preferred. However, the current literature models require still rigorous validation. The presented technique relies on optical tracking of a laser-tweezers trapped particle suspended in the liquid medium. The obtained experimental results for spherical particles of 1 micron diameter show a good agreement with the classical rheology and literature correlation models. The new method is a valuable tool for determination of sedimentation parameters as it reduces the time of experiments and the sample volume by order(s) of magnitude when compared to classical methods.